2015
DOI: 10.1016/j.resuscitation.2015.02.026
|View full text |Cite
|
Sign up to set email alerts
|

e-Learning in advanced life support – An evaluation by the Resuscitation Council (UK)

Abstract: day face-to-face course. e-learning access data were collected through the Learning Management System (LMS). All 53 participants were assessed by a multiple choice questionnaire (MCQ) before and after the face-to-face aspect 54 alongside a practical cardiac arrest simulation (CAS-Test). Participant demographics and assessment outcomes were 55 analysed. 56 57 Results 58The mean post e-learning MCQ score was 83.7 (SD 7.3) and the mean post-course MCQ score was 87.7 (SD 7.9). The 59 first attempt CAS-Test pass ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 33 publications
4
59
0
2
Order By: Relevance
“…84 This UK-based e-learning-ALS course was subsequently implemented and a further study of 27,170 candidates demonstrated equivalence to traditional instructor-led learning. 85 The online elearning program of 6-8 h was to be completed by candidates prior to attending a one-day modified instructor-led ALS-course. e-ALS scores were significantly higher on the pre-and postcourse MCQ and first attempt CAS-test pass rate was higher than compared to standard ALS courses (overall pass rate similar in both).…”
Section: Pre-course Training and Possible Alternatives Strategies To mentioning
confidence: 99%
“…84 This UK-based e-learning-ALS course was subsequently implemented and a further study of 27,170 candidates demonstrated equivalence to traditional instructor-led learning. 85 The online elearning program of 6-8 h was to be completed by candidates prior to attending a one-day modified instructor-led ALS-course. e-ALS scores were significantly higher on the pre-and postcourse MCQ and first attempt CAS-test pass rate was higher than compared to standard ALS courses (overall pass rate similar in both).…”
Section: Pre-course Training and Possible Alternatives Strategies To mentioning
confidence: 99%
“…Die Teilnehmer hatten ähnliche Bewertungen in der Wissensüberprüfung und den Fertigkeitseinschätzungen, und es gab keinen Unterschied im Bestehen bei Kursende, all dies bei Kostenreduktion um mehr als die Hälfte [84]. Dieses e-Learning-ALS-Kursformat wurde in Großbritannien flächen-deckend eingeführt und an 27.170 Teilnehmern die Gleichwertigkeit zu den traditionellen, ausschließlich mit Instruktoren besetzten Kursen aufgezeigt [85]. [89].…”
Section: Trainingsstrategien Auf Fortgeschrittenen-niveauunclassified
“…Indeed, a similar report from the UK had demonstrated that brief time course may be difficult for learning as the candidate age increases. So we need a long time course for enhancing resuscitation memory processing and updating the new knowledge and skills from latest guidelines [14]. Depending on this hypothesis, we had conducted a 1-day enhance course to consolidate knowledge concepts among primary mass CPR instructors.…”
Section: Discussionmentioning
confidence: 99%